Perkawinan Adat Merari’ Suku Sasak dalam Perspektif Hukum Adat : Studi Kasus di Desa Kateng Kecamatan Praya Barat Lombok Tengah - Amalia Solikha; Ismi Lailatul Maulida; Rahayu Sri Utami (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
Marriage is a universal social institution, yet its implementation is profoundly shaped by distinctive local cultural values. One such cultural manifestation is the Merari’ tradition practiced by the indigenous Sasak community in Central Lombok, West Nusa Tenggara. This tradition refers to the practice of "elopement," which forms an integral part of customary rituals uniting two individuals in marital bonds. This study aims to explore in depth the fundamental reasons why the Sasak people continue to uphold the Merari’ tradition amidst the tides of modernization and the bureaucratization of national marriage law. It also seeks to describe the procedural and normative structure of the Merari’ marriage process from the perspective of customary law. Furthermore, this research investigates the types of customary sanctions imposed when individuals violate the traditional norms of marriage. This study uses a socio-legal approach, which not only examines written legal norms (positive law) but also considers how these norms are applied and function within society, particularly through the practice of Merari’ in the Sasak community. The findings show that the Merari’ tradition is not merely a romanticized relic of the past, but a form of cultural resistance against the dominance of formal law, which is often perceived as inadequate in accommodating local values. The Merari’ process follows a clearly defined sequence—starting from mutual agreement between the couple, the act of elopement, reporting to customary leaders, and culminating in the nyelabar ceremony, which serves as the social ratification of the marriage. In cases of violation or deviation from these customary norms, community elders may impose sanctions such as traditional fines (material penalties), social exclusion, or prohibition from participating in customary events. Based on the analysis, it is concluded that the Merari’ tradition holds legal legitimacy within the framework of customary law, as it is carried out on the basis of social consensus, noble values, and binding communal norms. Its persistence illustrates a dynamic relationship between state law and customary law, wherein both systems can coexist in parallel, provided there is mutual recognition and space for dialogue. Thus, there is an urgent need for an integrative legal approach in the formulation of national legal policies—an approach that is not only normative, but also contextual and responsive to the legal pluralism present in Indonesian society.